Estimation Compression Strength of Concrete Made from Local Material Using Non-destructive Tests - Mohammed Ali Abdalla Elsageer , Salim Mohamed Eshtiwy , Mustafa Abougharsa (Journal of Pure & Applied Sciences, 2018)
The research focus on non-destructive testing on an ordinary concrete made of local materials (coarse and fine aggregate) which are obtained from the Jufrah area .Concrete mix design is done by using BRE method with different W/C ratio. Five concrete mixes design are made with different target compressive strength. The target compressive strength for three specimens cube at age 28 days was ranged between (10–60) MPa. Two non-destructive tests were done on the concrete specimens which are Schmidt hammer and Ultrasonic pulse velocity (UPV). Destructive test is conducted on concrete specimens in order to determine the concrete compressive strength, a relationships are obtained between Schmidt Hammer rebound number, Ultrasonic Pulse Velocity and cubes compressive strength of the local concretes.